PELAKSANAAN TES PSIKOLOGI MENGGUNAKAN COMPUTER ASISSTED TEST (CAT) DALAM REKRUTMEN SELEKSI BINTARA POLRI UNTUK MENGIKUTI SEKOLAH INSPEKTUR POLISI (SIP) DI POLDA SUMATERA SELATAN - Aprillia, Sesi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The quality of an organization's human resources greatly influences its competitive advantage. Therefore, in theory, human resource management views the recruitment and selection process as crucial for obtaining superior and competitive resources. Recruitment is a process or effort carried out to search for and collect a number of workers who have the skills according to needs or vacant positions to be employed in a company or in an organization. The method used in carrying out this test is an application-based computer assisted test (CAT) method. The results obtained in carrying out computer-based psychological tests using the computer assisted test method show that the implementation of the tests within the scope of the South Sumatra Regional Police has been said to be good and in accordance with the standards of the National Police Headquarters.